Preservation and Development Strategies of Gorontalo’s Local Culture through Gorontalo Cultural Digital Repository Application - Arip Mulyanto; Mukhlisulfatih Latief; Manda Rohandi; S Supriyadi (Mudra Jurnal Seni Budaya, 2016)
This study aims to implement a strategy of preservation and development of Gorontalo’s local culture through a web based application that can store and display the digitizing results of Gorontalo’s local culture called “Gorontalo cultural digital repository". The Gorontalo cultural digital repository provides information about the cultures in Gorontalo such as the mores, dances, historic sites and Gorontalo’s cultural artifacts in the form of video, images and text. The method used in this research is applied method withresearch procedures by: 1) Exploration, is to identify and analyze the data of local Gorontalo’s culture that covers Gorontalo’s mores, dances historic sites and Gorontalo’s cultural artifacts. 2) The development of Gorontalo cultural digital collection, which digitize the identification and analysis result of Gorontalo’s local culture. 3) Gorontalo Cultural Digital Repository application development. From the result of the research found: 1) Exploration the mores of Gorontalo consist of four important aspects, namely customarywelcoming guests, traditional coronation, marriage customs and funeral customs. There are more or less 20 historic sites located in Gorontalo. There are four dances that are usually performed in the customary celebration in Gorontalo.